Early Bronze Age IV Ceramic Regionalism in Central Jordan - Palumbo, Gaetano (Bulletin of ASOR, 1993)
The ceramic assemblages from tombs and excavations in Transjordan show typological and stylistic features that confirm the regional character of the Early Bronze IV culture. The relationships between established ceramic groups indicate that EB IV material culture in the upper Zerqa basin should be considered typologically distinct, comprising a new ceramic family, designated here as Amman-Zerqa (AZ).